The Effect of Extraction Temperature and Solvent to Oil Ratio on Viscosity Index of Mixed-medium Lubricating Oil Fraction by Using Solvents Extraction - A. Mohammed, Abdul-Halim; J. Yass Kheder, Mohammed (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
In this study two types of extraction solvents were used to extract the undesirable polyaromatics, the first solvent was furfural which was used today in the Iraqi refineries and the second was NMP (N-methyl-2-pyrrolidone). The studied effecting variables of extraction are extraction temperature ranged from 70 to 110°C and solvent to oil ratio in the range from 1:1 to 4:1. The results of this investigation show that the viscosity index of mixed-medium lubricating oil fraction increases with increasing extraction temperature and reaches 107.82 for NMP extraction at extraction temperature 110°C and solvent to oil ratio 4:1, while the viscosity index reaches to 101 for furfural extraction at the same extraction temperature and same solvent to oil ratio. The increase in solvent to oil ratio has a higher effect on increasing the viscosity index of lubricating oil fraction compared with extraction temperature in furfural and NMP extraction. Further more, the results show that the percentage yield of raffinate was decreased as the extraction temperature and solvent to oil ratio increases for furfural and NMP extraction.